Analiza inicjatyw organizacji rządowych i pozarządowych w Polsce wspomagających edukację formalną w zakresie kształcenia kompetencji medialnych i informacyjnych = Analysis of initiatives, governmental and nongovernmental organizations in Poland supporting formal education regarding vocational competencies in media and information - Piotrowska, Renata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
According to international documents, media and information education should be an integral part of the teaching process. Polish teachers declare that they have insufficient skills to make use of information and communication technologies in the teaching process. Studies of students [source of knowledge] prove that their media and information competences are largely limited. The study was conducted to see if and how governmental and non-governmental organizations support and complement formal education in the field of media and information literacy. 10 programs were selected from available governmental and non-governmental offers. The initiators of most of them are non-governmental organizations. Their primary goal can be realized through the parallel development of knowledge and skills of teachers and students. Synchronous e-learning courses are the dominant form of training during workshops, lectures and competitions. Programs are accompanied by a variety of materials and teaching aids. Most of them are made available on free licenses for use by teachers in their professional work.
Keywords: edukacja informacyjna; edukacja medialna; kompetencje cyfrowe; kompetencje informacyjne; programy i projekty rządowe; organizacje pozarządowe (NGO); information education; media education; digital competences; information competences; government programs and projects; non-governmental organizations